Causes of Initiation of Methamphetamine Use in Khyber Pakhtunkhwa, Pakistan: A Qualitative Study - Khaliq Jan, Sameer Ul; Ali, Ahmad; Niqab, Muhammad; Iqbal, Shahid (Addicta: The Turkish Journal on Addictions, 2022)
Methamphetamine is a powerful stimulant drug, and its use has increased in the last decade in Pakistan. The purpose of the current qualitative study was to explore the responsible factors associated with the initiation of methamphetamine use in Khyber Pakhtunkhwa, Pakistan. The participants of the study were the officials of 14 Drug Rehabilitation Centers and Anti-Narcotic Force, Peshawar city, Pakistan. Data were collected through an interview guide, and each participant was selected through a purposeful sampling technique in 2020. The collected data were analyzed, and themes and sub-themes were extracted from it. The study found that four main causes are responsible for the initiation of methamphetamine as follows: (i) easy availability, (ii) peer influence, (iii) curiosity, and (iv) exam preparation. The study recommends that family may play a key role in the prevention of drug use, and public awareness should be created about the misconceptions and toxicity of methamphetamine use.
Keywords: Causes; initiation; methamphetamine; Pakistan; qualitative study